Parametric studies of ring and parallel coupled line resonators for matched bandstop filter design - Abdullah Mohammed Zobilah; Adib Othman; Noor Azwan Shairi; Zahriladha Zakaria (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Recently, matched bandstop filters had become a substantial part of modern RF and microwave systems. However, in these types of filters, the key problem in the couplings of any microstrip resonators to transmission microstrip line is the variation or tolerance of the coupling gap. It was found that the bandstop response is very sensitive to the gap size of the coupled line. Therefore, this paper presents parametric studies of dual-mode parallel coupled line and ring resonator for matched bandstop filter design. For parallel coupled line resonator, it was found that with careful design and proper circuit parametric study on the coupling spacing, very high notch and matched return loss response were obtained. In contrast, for ring resonator, based on the simulated result, it was found that a very high notch and matched return loss response were obtained with careful design and proper circuit parametric study on the coupling spacing, width at coupling lines, and perturbed stub length.